Proposed literature review on ASIA pacific university assignment submission and feedback system for future development - Eaganathan, Umapathy; Md. Maruf Hasan, Syed (International Journal of Engineering and Technology, 2018)
This paper will explain about the proposed literature review about assignment submission system for Asia Pacific University, Malaysia. Currently this university operating to receive assignments from students directly also students need to be in queue by spending time for the submission of assignment. Still most of the universities here in Malaysia following traditional way to manage studentâ€™s assignments within a given time frame. Thus, students are facing many troublesome issues while submitting their assignments. Wasting money is one the most important issues while submitting assignment. They need to print and bind then submit at admin desk which is sometime costly. Besides, day by day living cost is becoming expensive compare to previous time. So, it is impossible for students to cope up with so much expenses. The main aims to help students to understand the importance of submitting assignments on time as well as reinforcing the essential skill of time management, so that students are aware of the importance of submitting assignments on time despite any circumstances. Here proposed the literature review in detail for the future development of easy assignment submission system for Asia Pacific University, Malaysia.Â